A transgenic DND1GFP fusion allele reports in vivo expression and RNA-binding targets in undifferentiated mouse germ cells. Issue 4 (4th January 2021) - Ruthig, Victor A; Yokonishi, Tetsuhiro; Friedersdorf, Matthew B; Batchvarova, Sofia; Hardy, Josiah; Garness, Jason A; Keene, Jack D; Capel, Blanche
Abstract: In vertebrates, the RNA-binding protein (RBP) dead end 1 (DND1) is essential for primordial germ cell (PGC) survival and maintenance of cell identity. In multiple species, Dnd1 loss or mutation leads to severe PGC loss soon after specification or, in some species, germ cell transformation to somatic lineages. Our investigations into the role of DND1 in PGC specification and differentiation have been limited by the absence of an available antibody. To address this problem, we used CRISPR/Cas9 gene editing to establish a transgenic mouse line carrying a DND1 GFP fusion allele. We present imaging analysis of DND1 GFP expression showing that DND1 GFP expression is heterogeneous among male germ cells (MGCs) and female germ cells (FGCs). DND1 GFP was detected in MGCs throughout fetal life but lost from FGCs at meiotic entry. In postnatal and adult testes, DND1 GFP expression correlated with classic markers for the premeiotic spermatogonial population. Utilizing the GFP tag for RNA immunoprecipitation (RIP) analysis in MGCs validated this transgenic as a tool for identifying in vivo transcript targets of DND1. The DND1 GFP mouse line is a novel tool for isolation and analysis of embryonic and fetal germ cells, and the spermatogonial population of the postnatal and adult testis. Abstract : Characterization of this novel transgenic mouse showed that DND1GFP is expressed throughout the pre-meiotic germline, supports growing evidence in the field of germ cell heterogeneity, and demonstrated the tagged allele can be used for identification of DND1 targets.